1993
DOI: 10.1002/eji.1830231121
|View full text |Cite
|
Sign up to set email alerts
|

The Vχ genes of the L regions and the repertoire of Vχ gene sequences in the human germ line

Abstract: Only 14 of the 25 V kappa genes and pseudogenes had been found before as parts of the L regions. The cloning and linking described in the accompanying report allowed us now to assign to Lp or Ld some V kappa genes which had been found before on scattered clones. In addition the sequences of several still unknown genes are reported here, thus completing the publication of the V kappa genes of the kappa locus as far as they are potentially functional or have only one or two 1-bp defects. Of the V kappa genes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…For humans, such analyses are robust because the number of functional germ-line V H genes is relatively few (Ϸ43 and 51 for IMGT and VBase databases, respectively), and the corresponding loci have been sequenced (26)(27)(28)(29). However, for mice, these analyses are less precise because the germ-line IgV repertoire is much larger (Ϸ300 V H genes; refs.…”
Section: Results (I) Characteristics Of Bcrs Expressed By Leukemic B mentioning
confidence: 99%
“…For humans, such analyses are robust because the number of functional germ-line V H genes is relatively few (Ϸ43 and 51 for IMGT and VBase databases, respectively), and the corresponding loci have been sequenced (26)(27)(28)(29). However, for mice, these analyses are less precise because the germ-line IgV repertoire is much larger (Ϸ300 V H genes; refs.…”
Section: Results (I) Characteristics Of Bcrs Expressed By Leukemic B mentioning
confidence: 99%
“…4%) was found with the germ-line gene L2. It is worth noting that SCI LC was also related to the same family of germ-line genes, family IIIa, which is often expressed in autoantibodies with rheumatoid factor activity [18,19]. Alignment of the N-terminal amino acid sequence of protein REV with known protein sequences showed that it was shorter by one residue than all previously reported -chains and begun with the normal Ile2 residue of the V III subgroup (according to Kabat's numbering [15]).…”
Section: Discussionmentioning
confidence: 99%
“…1. The V H sequence was encoded by the DP7 segment (V H 1 family) (55); and the V L sequence by the L12a segment (V k 1 family) (56). About 5 mg of scFv7 protein was purified from 1 liter of bacterial supernatant by immobilized metal chelate affinity chromatography, and was judged to be about 90% pure, by SDS-PAGE (not shown).…”
Section: Isolation Of Scfvs With Affinity For the Ovr From A Phagementioning
confidence: 99%